1995
DOI: 10.1071/rd9951329
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of 11 beta-hydroxysteroid dehydrogenase in ovine fetal kidney and lung

Abstract: Eleven-beta-hydroxysteroid dehydrogenase (11 beta-HSD) is an enzyme which degrades 11-hydroxycorticosteroids to biologically inactive 11-oxocorticosteroids (cortisone and 11-dehydrocorticosterone). In some tissues, the activity of this enzyme prevents binding of cortisol to mineralocorticoid receptors. The present experiments were designed to test the hypothesis that the fetal kidney contains 11 beta-HSD, that the activity of 11 beta-HSD in fetal kidney increases near term, and that the fetal lung does not con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…This finding is consistent with previous observations that showed no alteration in renal 11 -HSD2 mRNA abundance in fetal sheep over this period of late gestation . However, earlier studies have shown an increase in both renal 11 -HSD2 gene expression and activity between 80-100 days and term (Wood & Srun 1995, Langlois et al 1995. Taken together, these observations suggest that renal 11 -HSD2 activity may rise during nephrogenesis which occurs throughout mid to late gestation but is complete by about 130 days of gestation in the sheep (Wintour 1997).…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…This finding is consistent with previous observations that showed no alteration in renal 11 -HSD2 mRNA abundance in fetal sheep over this period of late gestation . However, earlier studies have shown an increase in both renal 11 -HSD2 gene expression and activity between 80-100 days and term (Wood & Srun 1995, Langlois et al 1995. Taken together, these observations suggest that renal 11 -HSD2 activity may rise during nephrogenesis which occurs throughout mid to late gestation but is complete by about 130 days of gestation in the sheep (Wintour 1997).…”
Section: Discussionsupporting
confidence: 48%
“…The 11 -HSD1 isoform is found in a number of adult tissues while 11 -HSD2 is present primarily in aldosterone-sensitive tissues, such as the kidney, colon and salivary glands (White et al 1997, Burton & Waddell 1999. Studies in several species including the sheep have shown a similar distribution of 11 -HSD isoforms in fetal tissues with high 11 -HSD2 expression in the fetal kidneys (Langlois et al 1995, Stewart et al 1995b, Wood & Srun 1995, Brown et al 1996.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…In comparison, 11 -HSD type 2 is a unidirectional NAD + -dependent dehydrogenase that converts cortisol to cortisone (Rusvai & Naray-Fejes-Toth 1993). Thus the expression of 11 -HSD isoenzymes and the direction of activity may be important in the local regulation of corticosteroid concentrations within glucocorticoid target tissues (Whorwood et al 1993, Rajan et al 1996 such as liver (Tannin et al 1991, Jamieson et al 1995, lung (Hundertmark et al 1995, Wood & Srun 1995, placenta , adipose tissue (Bujalska et al 1997, Rask et al 2001, gonad (Ricketts et al 1998b) and the central nervous system (Kim et al 1995). In the fetal sheep liver 11 -HSD1 was highly expressed, whereas 11 -HSD2 mRNA and activity were undetectable .…”
Section: Introductionmentioning
confidence: 99%